The Use of Audio-Visual Media in Learning Social Studies to Improve the Learning Outcomes of Grade V Students at Lebak Kepuh 2 Elementary School - Karmila, Karmila; Nurkhasanah, Nurkhasanah; Rostika, Rostika (Jurnal Primagraha, 2023)
The purpose of this study was to describe the use of audio-visual media that can improve learning outcomes in social studies learning for student of SDN Lebak Kepuh 2. This type of research is interview research or observation. The subjects in this study all class V grade students SDN Lebak kepuh 2 which totalled 20 people, with 11 men and 9 women. This research procedure uses interview, observation and documentation of data collection techniques used are observation and tests. The data analysis technique uses the presentase (%) formula while the results of this study are using audio-visual media can improve social studies learning achievement in landscape material in grade 5 students at SDN Lebak Kepuh 2, Serang district. In the research result, it was found that the success rate of student learning outcomes achieved a score of >75 by 15 students (75%) and <75 by 5 students (25%). Based on student learning outcomes, there is an increase in student understanding, this was proven after the use of audio-visual media in social studies learning in grade 5 SDN Lebak Kepuh 2.